Effects of material hardship on depression among adults in South Korea: insights from by the Korea Welfare Panel Study 2008-2017 - Soo Hyun Kang; Selin Kim; Eun-Cheol Park; Sung-In Jang (BMC, 2021)
Abstract Background Low socioeconomic status deemed by income-based measures is a risk factor for depression. Material hardship is commonly used as a multidimensional socioeconomic indicator to identify the struggles that low-income households encounter that are not captured by conventional income-based measures. The aim of this study was to examine the effect of material hardship on depression. Methods We used wave 3 (2008) to wave 12 (2017) panel data collected by the Korea Welfare Panel Study. The material hardship measure included six dimensions: food, housing, medical care, paying utility bills, education, and financial hardship. Depression was measured using the Center for Epidemiologic Studies Depression Scale (CESD-11). A generalised estimating equation model was applied to test the causal association between material hardship and log transferred CESD-11. Results The first time point comprised 3,866 participants. Those who continually experienced material hardship had higher depression scores (male: β = 2.82, female: β = 3.98, p-value: < .0001). Food hardship was the most critical risk factor (male: β = 3.29, female: β = 4.05, p-value: < .0001). Conclusions Material hardship is associated with increased risk of depression, especially food hardship. We should consider guaranteeing food security, and community and policy makers should consider material hardship in their approach when identifying low-income populations at high risk for depression.